Soil-transmitted helminthes prevalence, intensity, and associated factors among school-aged children in the communities of west Guji Zone, South Ethiopia - Tibeso Gemechu; Wako Dedecha; Alqeer Aliyo; Abdistion Disani; Feven Diriba (Clinical Epidemiology and Global Health)
Background: Soil-transmitted helminth (STH) infections are a major health problem among school-age children in developing countries. Prolonged exposure to STH can lead to reduced physical fitness, stunted growth, anemia, bowel obstruction, and cognitive impairments. Objective: To determine the prevalence, intensity, and associated risk factors of soil-transmitted helminths among school-aged children in the west Guji Zone, South Ethiopia. Methods: A community-based cross-sectional study was conducted among 614 randomly selected school-aged children in selected districts of the West Guji zone from February to March 2023. A pre-tested questionnaire was used, and samples were examined by wet mount and Kato-Katz techniques. Data entry was analyzed using SPSS. Binary and multivariable logistic regression analyses were applied to identify potential associated factors. P-value<0.05 was declared as statistical significance. Results: The overall prevalence of STH was 32.7 % (95 % CI: 28.4%–35.8 %). Ascaris lumbricoides 95 (11.1 %) was the most common identified STH. Most school-age children, 74 %, were infected with a mild intensity of soil-transmitted helminths (STH). The mean egg count for Ascaris lumbricoides, Trichuris trichiura, and hookworms was 4465.4, 563.7, and 958.9, respectively. The study found significant associations with several factors, including washing hands with soap after using the toilet (AOR: 2.8, 95 % CI: 1.8–4.6), trimming fingernails (AOR: 4.6, 95%CI: 2.9–7.1), and the habit of wearing shoes (AOR: 2, 95%CI: 1.4–2.9) Conclusion: Soil-transmitted helminths infection prevalence is high among school-aged children of the study areas. To prevent and control these infections, comprehensive health education should focus on the importance of hygienic practices, improved sanitation, and regular deworming programs for school-aged children.